Patient and Caregiver Perceptions on the Allocation Process and Waitlist, and Accepting a Less-Than-Ideal Kidney: A Canadian Survey - Marie-Chantal Fortin; Fabian Ballesteros Gallego; Héloise Cardinal; Manpreet Kaur; Rahul Mainra; Sylvain Patoine; Nicola Rosaasen; Holly Mansell (Canadian Journal of Kidney Health and Disease)
Background: Transplanting less-than-ideal (LTI) kidneys could help optimize organ utilization, but little is known about how patients and caregivers perceive the allocation process, waitlist, or LTI kidneys. Objective: To explore the perspectives of patients and caregivers on the Canadian kidney transplant allocation process, waitlist, and LTI kidneys. Design: Electronic survey. Setting: Canada. Patients: Transplant recipients, candidates, and caregivers. Methods: A bilingual electronic national survey was administered from January to March 2024. The questionnaire contained sections on demographics, perceptions of organ allocation and acceptance, LTI kidneys, and educational preferences. Descriptive analysis was performed. Results: Two hundred fifty-one responses were analyzed, including patients (63%, n = 159), and caregivers (37%, n = 92), from 11 provinces and territories. Three-quarters (74%, n = 186) understood how patients are placed on the waiting list, and 65% (n = 162) understood how donor kidneys are allocated, but 72% (n = 181) and 68% (n = 171) wanted more information about the waitlist and donor kidney allocation criteria, respectively. Approximately 20% felt that the waitlist and allocation processes were not transparent. Awareness about the option to refuse a deceased donor kidney offer was high (69%, n = 174), yet nearly half of respondents (46%, n = 115) expressed concern about being disadvantaged if an offer for a deceased donor kidney was refused. One-third of participants (33%, n = 83) were open to accepting an LTI kidney. Limitations: Compared to the general population, more study participants were white, and the majority were educated and financially at ease. This limits the generalizability of the results. Conclusion: Enhanced communication is required to improve transparency and information about the allocation system and waitlist in Canada.